Antibacterial Effectiveness Test of Methanol Extract of Red Galangal Rhizome (Alpinia purpurata (Vieill) K. Schum) Against Streptococcus pyogenes and Klebsiella pneumonia Bacteria - Dwi Permatasari Utomo Putri; Listiana Masyita Dewi; Rochmadina Suci Bestari; Nurhayani (HM Publisher, 2024)
Red galangal rhizome (Alpinia purpurata (Vieill) K. Schum) is a medicinal plant belonging to the family Zingiberaceae. Red galangal rhizomes have antibacterial benefits because they contain active substances such as flavonoids, saponins, triterpenoids, alkaloids, and tannins. Streptococcus pyogenes causes bacterial infections of the skin and upper respiratory tract, while Klebsiella pneumonia is the bacteria that causes pneumonia. This study aims to determine the antibacterial effectiveness of methanol extract of red galangal rhizomes (Alpinia purpurata (Vieill) K. Schum) against Streptococcus pyogenes and Klebsiella pneumonia bacteria. This research is an experimental laboratory with a post-test-only controlled group design. Red galangal rhizomes were extracted using methanol solvent and tested for antibacterial effectiveness using the well method. There were 6 groups in the study, namely the chloramphenicol positive control group, the distilled water negative control group, and the 20%, 40%, 60%, and 80% concentration groups. The largest inhibition zone diameter was found at a concentration of 80%, with an average of 25.50 mm in Streptococcus pyogenes bacteria and 28.73 mm in Klebsiella pneumonia bacteria. In conclusion, methanol extract of red galangal rhizome (Alpinia purpurata (Vieill) K. Schum) effective against bacteria Streptococcus pyogenes and Klebsiella pneumonia.